KOMUNIKASI NON VERBAL SEBAGAI SOLUSI MENINGKATKAN PERKEMBANGAN BAHASA ANAK AUTIS - Anita Solihatul Wahidah, M.Pd.I, M.Si (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
Abstract The language limitations experienced by autistic children encourage them to form appropriate communication patterns to be able to build and develop autistic children's communication as the main medium of interaction with the environment, one of which is non-verbal communication. This background makes researchers conduct research on non-verbal communication, the right solution to improve the language of children with autism. This study uses descriptive qualitative research methods, namely research methods that describe, describe and interpret the object under study systematically so that researchers can find out how to apply non-verbal communication to improve communication skills of autistic children. This research method uses data collection techniques through observation or observations and interviews. The data analysis technique used in this research is descriptive qualitative by interpreting the data in the form of observations and interviews obtained. The results of the study concluded that to improve the language skills of autistic children, a teacher could use non-verbal communication. The forms of non-verbal communication that teachers often use are facial expressions, body and hand movements, touch, and proximity. And for the results of observations, it is known that some autistic children have increased, such as: being able to pronounce words fluently without stuttering, getting more fluent in language even though they are still slurred, because to improve the condition of the lisp it is not enough in a short time, the ability to socialize has also experienced improvement after being invited to fantasy exercise together, having started to be able to focus and say words according to the teacher's orders, the behavior of children who used to be difficult to control has now decreased because the focus of children's attention has increased to the teacher as a source of communication after the teacher keeps a close distance with them. Keywords: Non-Verbal Communication, Language Development of Autistic Children